Anti-inflammatory properties of ethanolic extract from Vatairea macrocarpa leaves. (5th October 2021) - Santos, Elisangela dos; Silva-Filho, Saulo Euclides; Santos Radai, Joyce Alencar; Arena, Arielle Cristina; Fraga, Thiago Leite; Lima Cardoso, Cláudia Andrea; Croda, Julio; Leite Kassuya, Cândida Aparecida
Abstract: Ethnopharmacological relevance: In Brazilian traditional folk medicine, the leaves and heartwood from Vatairea macrocarpa (Benth) Ducke (Angelim-of-Cerrado) (Fabaceae family) are used as remedy after cold maceration for the treatment of the condition popularly known as rheumatism, as well as for the general inflammatory aspects such as pains, injury and swelling. The rheumatological and rheumatic diseases affect 0.3–1.0% of the world population and all long-term treatment with conventional medications lead to adverse effects. Aim of the study: To investigate the chemical composition and the anti-inflammatory properties and of the ethanolic extract from V. macrocarpa leaves (EEVM) in experimental models. Material and methods: EEVM was chemically analyzed by spectrophotometry and the compounds characterization was performed by nuclear magnetic resonance and mass spectrometry. EEVM was evaluated in methylthiazolyldiphenyl-tetrazolium bromide (MTT) (3, 10, 30, and 90 μg/ml) and neutrophils phagocytic activity (1, 3, and 10 μg/ml) tests. For in vivo models, the EEVM (10, 30, 100, and 300 mg/kg) was orally administered (p.o.) for inflammatory evaluation in carrageenan-induced pleurisy in Swiss mice. The EEVM (30 and 100 mg/kg, p.o.) was tested against the Complete Freund Adjuvant (CFA)-induced paw persistent inflammation and Mycobacterium bovis (bacillus Calmette-Guerin - BCG)-induced pleurisy in C57bL6 mice. Results: The chemical composition of EEVM showed 157.06 mg (GAE)/g in relation to phenolic compounds, 82.13 mg (RUE)/g in relation to flavonoids and 48.99 mg (TAE)/g in relation to tannins. The flavonoid compounds identified were catechin, epicatechin and kaempferol-3-O-a-l-rhamnopyranoside. EEVM did not present cytotoxicity in MTT assay, however EEVM reduced phagocytic neutrophils activity at all tested concentration. EEVM significantly inhibited leukocytes migration/proteins exudation in carrageenan-induced pleurisy model. The daily administration of EEVM inhibited the inflammatory parameters in BCG and CFA models. Conclusions: The present study showed anti-inflammatory features of EEVM ( V. macrocarpa ) as a natural agent against inflammatory diseases. Graphical abstract: Image 1